STRATEGY TO ENHANCE ORGANIZATIONAL COMMITMENT FOR THE SUSTAINABILITY OF CULINARY SMALL AND MEDIUM ENTERPRISES IN BOGOR CITY - Roosganda Elizabeth; Didik Notosudjono; Hamzah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Culinary small and medium enterprises (SMEs) play a vital role in Indonesia’s economy, contributing to GDP, employment, and community income. This dissertation research is significant as it identifies sustainability challenges resulting from low komitmen terhadap organisasi, influenced by variables such as perceived organizational support and creativity, with work motivation acting as a mediating factor. Moreover, there has been a lack of specific studies addressing this issue. The objective of this research is to analyze the influence of the three variables on komitmen terhadap organisasi and to formulate strategic approaches to enhance the sustainability of culinary SMEs in Bogor City.Seven hypotheses are proposed, examining the influence of perceived organizational support and creativity on work motivation and komitmen terhadap organisasi, as well as the mediating role of work motivation in these relationships. The novelty of this research lies in its strategic framework for enhancing komitmen terhadap organisasi to ensure business sustainability and its integration of the three exogenous variables into a validated analytical model. A mixed-method approach was employed, involving 230 employee respondents from Bogor City, collected between December 2023 and July 2024. The findings reveal that perceived organizational support affects komitmen terhadap organisasi through the mediation of work motivation. Additionally, both creativity and work motivation have a direct influence on komitmen terhadap organisasi. Furthermore, five strategic recommendations were developed to support the sustainability of culinary SMEs. It is expected that the results of this dissertation can serve as a foundation and guide for academics, entrepreneurs, and policymakers in formulating more effective policies to improve the sustainability and competitiveness of culinary SMEs at both the national (Bogor and Indonesia) and international levels.